The Perception of the Menopause and Climacteric among Women in Hong Kong and Southern China - Haines, C. J. (Institutional Knowledge at Singapore Management University, 1995)
A lack of awareness of the long-term consequences of the menopause may be a major contributing factor to the low demand for hormone replacement therapy in Hong Kong and China. Most Chinese women suffer few acute menopausal symptoms, and it was our hypothesis that they had little knowledge of the risks of developing either osteoporosis or cardiovascular disease as a result of estrogen deficiency. Methods. A prospective study was conducted among 200 Chinese women of all ages living in Hong Kong or southern China. A structured questionnaire was used to examine their perception of the menopause and the climacteric. Results. While 96% of women from Hong Kong and 73% from southern China could define the menopause, none in either group were aware of the problems of either osteoporosis or cardiovascular disease in postmenopausal women. Only 8% of women from Hong Kong and 4% from southern China knew that hormone replacement therapy could be used to treat postmenopausal women. Conclusions. The results of this study confirm a relative lack of understanding of the climacteric in both groups of Chinese women. As menopausal symptoms are also infrequent in this population, most women will not have the need to consult a physician and will therefore not have the option of taking hormone replacement therapy to prevent the long-term effects of estrogen deficiency. Considering the sizes of the populations involved, the potential for reducing morbidity and mortality through improved education about the menopause is considerable.